The Effect of Brand Image, Product Quality, and Price on Thriftshop Clothing Purchasing Decisions in Medan City (Case Study @cchase.id) - Gunawan, Danish Irsyad; Ramadhani, Sri; Harahap, Muhammad Ikhsan (Universitas Islam Kadiri, 2024)
Secondhand clothing, especially among teens, has become more fashionable because most people consider it unique and classic. Indonesia sold more imported used garments due to their higher quality and lower price. Demand for imported used clothes is rising. Fans and customers can buy affordable, wearable famous brand outfits. This study examines how brand image, quality, and price affect buying decisions. This quantitative study collects data using a questionnaire and analyzes it using IBM SPSS Software. Probability and puposive sampling were utilized in this investigation. Research instrument tests, classical assumption tests, model accuracy tests, multiple linear analysis, and partial tests are used in data analysis. Brand image, product quality, and price influence Medan City Thriftshop clothes purchases, according to Hasi research. Brand image strongly influences used apparel purchases. Brand image t test has 0.000 0.05 significant level and 3.904> 1.655 tcount> ttable value. Product quality strongly influences used clothing purchases. The t-test results for product quality indicate a significance level of 0.000 <0.05 and a tcount> ttable value of 1.747> 1.655. Price strongly influences used clothing purchases. The t-test results for the price variable indicate a significance level of 0.000 < 0.05 and a tcount value of 3.753> 1.655 Thus, brand image, quality, and pricing influence purchases